2004
DOI: 10.1143/jjap.43.3981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ester Groups on Proton Generation and Diffusion in Polymethacrylate Matrices

Abstract: The control of acid generation and diffusion is essential for the improvement of resist performance based on the chemical amplification concept. Polymethacrylates are excellent matrices to study resist reaction mechanisms. The dependence of polymer structure on acid generation and diffusion was investigated using polymethacrylate matrices. The ester groups of the polymers strongly affect the yield and diffusion of protons. This suggests that the yield and the diffusion constant of the acid can be controlled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…12 Therefore, the probability density of acid can be assumed to be approximately same as counter anion distribution, although the deprotonation reaction highly depends on polymer structures. [15][16][17] Assumed that the deprotonation efficiency of radical cations is 100 %, the acid generation probabilities per an ionization incident are 0.68 (r 0 = 4) and 0.76 (r 0 = 6). The average distances between ionization points and acids are 6.0 (r 0 = 4) and 8.0 nm (r 0 = 6).…”
Section: Resultsmentioning
confidence: 99%
“…12 Therefore, the probability density of acid can be assumed to be approximately same as counter anion distribution, although the deprotonation reaction highly depends on polymer structures. [15][16][17] Assumed that the deprotonation efficiency of radical cations is 100 %, the acid generation probabilities per an ionization incident are 0.68 (r 0 = 4) and 0.76 (r 0 = 6). The average distances between ionization points and acids are 6.0 (r 0 = 4) and 8.0 nm (r 0 = 6).…”
Section: Resultsmentioning
confidence: 99%
“…This electron is then trapped by PAG through reductive electron transfer and activates PAG to generate acid. It has been reported that acid generation yield under EUV exposure is strongly affected by polymer structure [27][28][29][30][31]. PAG structure [32][33][34] and its loadings [33,34], respectively.…”
Section: El (%)mentioning
confidence: 99%
“…Sensitization mechanism of EUV resist has been well investigated by many researchers [30][31][32][33][34][35][36][37][38][39][40]. Absorption of high-energy EUV light (13.5 nm) mainly by polymer is the first step of EUV sensitization.…”
Section: Noise Mitigation Approach (1): Dissolution Uniformity Of Nbamentioning
confidence: 99%
“…This electron is then trapped by PAG through reductive electron transfer and activates PAG to generate acid. It has been reported that acid generation yield under EUV exposure is strongly affected by polymer structure [32][33][34][35][36], PAG structure [37][38][39], and its loadings [38][39][40], respectively.…”
Section: Noise Mitigation Approach (1): Dissolution Uniformity Of Nbamentioning
confidence: 99%